(untitled) (Bangladesh Medical Journal, 2026)
Proximal humerus fractures are common injuries with a wide range of surgical treatment options, particularly for displaced fractures. Comparative data on functional outcomes following different surgical modalities are therefore clinically relevant. This study evaluated functional outcomes after surgical management of proximal humerus fractures and examined the association between surgical modality and recovery at 6 months. This prospective observational study was conducted for one and a half years at the Department of Orthopedic Surgery, Sir Salimullah Medical College Mitford Hospital (SSMCMH), from January 2022 to June 2023, among 95 adult patients with surgically managed proximal humerus fractures. Open reduction and internal fixation (ORIF) with locking compression plate (LCP), K-wire fixation, intramedullary (IM) nailing, and hemiarthroplasty were performed according to fracture characteristics, bone quality, and surgeon preference. The study population consisted predominantly (58.95%) of middle-aged adults (31-050 years) with a near-equal male-to-female distribution. Road traffic accidents accounted for approximately 41% of injuries, followed by falls (25%). Two-part fractures constituted just over half of cases, followed by three-part fractures, with four-part fractures forming a smaller proportion. ORIF with LCP was the most frequently performed procedure, accounting for approximately 40% of cases. At 6 months’ follow-up, the functional outcomes were evaluated using Neer’s shoulder score; the mean pain, function, and anatomical alignment scores were about 33, 16, and 6, respectively. Unadjusted analyses demonstrated higher mean pain, range of motion, and anatomical alignment scores among patients treated with ORIF using LCP compared with other surgical modalities. Multivariable linear regression analyses adjusted for age, sex, fracture pattern, comorbidities, side of involvement, and delay to surgery showed that K-wire fixation was associated with lower pain, range of motion, and anatomical alignment scores compared with LCP fixation. IM nailing demonstrated smaller but statistically significant reductions across all domains, while hemiarthroplasty showed the largest negative associations, particularly for range of motion and anatomical alignment. Overall, ORIF with LCP fixation was associated with higher short-term functional outcome scores compared with K-wire fixation, IM nailing, and hemiarthroplasty. As inferential analyses were conducted using a simulated patient-level dataset constructed from study-level aggregates, these findings should be interpreted as hypothesis-generating and require confirmation using complete patient-level data. Bangladesh Med J. 2025 Sept; 54(1): 23-29